2021
DOI: 10.18596/jotcsa.894374
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Polymeric Materials that can be Used to Prevent Metal Corrosion: A Review

Abstract: Traditional study has discovered that natural materials such as wood are scarce and that synthetic materials can serve as suitable substitutes. Polymer chemicals, plant materials, chemical compounds, inorganic compounds, and other corrosion inhibitors all use metals. When technology fails, corrosion is one of the most severe consequences, causing harm to the financial system, natural resources, and people's lives. Natural materials such as wood are scarce, according to traditional research, and synthetic mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…As illustrated in the two figures, the specimens demonstrated lower hardness after immersion in the corrosive media when compared to their hardness values before immersion. This is an indication that the chemical/electrochemical reactions of all the salt solutions affected the surfaces of the specimens[1], which enhanced indentation of the specimens. It has been reported that early stages of corrosion largely depends on roughness of the surfaces of metals/alloys because dense oxide films on metals or alloys surfaces that are protecting the metals or alloys from corrosion can be easily destroyed at high surface roughness[22].…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…As illustrated in the two figures, the specimens demonstrated lower hardness after immersion in the corrosive media when compared to their hardness values before immersion. This is an indication that the chemical/electrochemical reactions of all the salt solutions affected the surfaces of the specimens[1], which enhanced indentation of the specimens. It has been reported that early stages of corrosion largely depends on roughness of the surfaces of metals/alloys because dense oxide films on metals or alloys surfaces that are protecting the metals or alloys from corrosion can be easily destroyed at high surface roughness[22].…”
mentioning
confidence: 95%
“…Corrosion is an irreversible interfacial reaction of a material (metal, ceramic, and polymer) with its environment, which results in its consumption or dissolution into the material of a component of the environment. Often, but not necessarily, corrosion results in effects that are detrimental to the usage of the material considered [1]. When the surfaces of materials deteriorate due to chemical reactions with their surroundings, corrosion has taken place.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations